Dosimetric treatment planning in nuclear medicine therapies. (September 2016) - Sarti, G.; Fabbri, C.; Busca, F.; Del Dottore, F.; Sanniti, S.
Abstract : Introduction: Dosimetric studies are presented for the 90Y Radiopeptide therapy and the 131I thyroid treatments. Purpose: In the 131 I thyroid treatments, the PreTherapeutic dosimetry has the purpose of identifying the optimal activity to be administered to the target in a single solution and in the metastases to evaluate the dose to red marrow. In the Radiopeptide therapy timed in 6–8 cycles, after the first and last cycle PostTherapeutic Dosimetric verification is performed. Materials and methods: CT-PET and CT-SPECT systems were characterized for the activity quantification for dosimetrIc evaluation Sensitivity in cps/MBQ, reproducibility and linearity Partial volume post imaging correction, Recovery Coefficients curves with method isovolume ecc. Segmentation method of the targets with variable threshold at differents Lesion/Background ratios 3D uniformity analysis Results: For lesions of known volume >5 ml and homogeneous distributions, the error associated with the evaluation of the activity may be regarded as not higher than 20% For lesions of volume not known, for target segmentation we use the method to variable threshold Verification of non-uniform 3D distributions of activity is affected by the low uniformity tomographic (30%). In 90Y PET/CT, quantification (MBq/ml) was in presence of a minimum detectable activity concentration (0, 2–0, 7 MBq/ml). Conclusions: The error associated with the absolute quantification for the radioisotopes gamma emitter and for 90 Y (Bremsstrahlung SPECT-CT or low sensitivity PET-CT) is within about 20%.